The Criminal Regulation on Narcotics Abuse Based on Restorative Justice Arrangements - Sri Sulistyawati (UNISSULA, 2023)
The drug abuse itself is divided into three categories, namely self-abuse, victims of drug abuse, and drug addicts who do not report. The purpose of this study is to find out about the settlement of narcotics abuse cases using restorative justice which is considered fair and balanced. The approach method used is normative juridical, with the nature of descriptive-analytic research. the results of the research and discussion state that the settlement of narcotics abuse with restorative justice is needed for the value of justice for abusers, but laws and regulations are needed that specifically regulate restorative justice as a legal umbrella for existing regulations in the application of restorative justice for narcotics abuse so as not to cause confusion in its application. This means that settling a narcotics misuse offence through restorative justice cannot occur unless all of the conditions outlined in the regulations are met and all of the parties concerned are in agreement.